The Mentoring of Health Cadres in Toddler Caring of Durian Posyandu at Karangduren Village, Pakisaji District - Harini, Ririn; Juwitasari, Juwitasari (Journal of Community Service for Health, 2021)
Fifteen health cadres at Karangduren village, Pakisaji, southern part of Malang East Java, face problems such as the lack of ability and confidence in providing health information to the mothers who visit the posyandu regarding to baby and toddler care. This community service was conducted to provide skill provisions for toddler health cadres in performing education for mothers of toddler as well as skill learning about baby care. Therefore, it was done by having mentoring and provisioning to the health cadres with 3 activities based on the problems which included the unavailability of health support facilities for cadres by having the mentoring activity for the health cadres, completing the lack of infrastructure and the unavailability of trained health cadres from the mothers of toddler. The results obtained from the mentoring showed significant improvement of knowledge from the entire participants of mentoring, which could be observed from the properly applied skills in baby/toddler care. It could also be observed from the facilities added such as the educational game tools (APE) which proved that cadres can select games that stimulate toddlers in improving their cognitive, affective and motor growth. Overall, it could be stated that the program achieved 90% of achievement which could be aimed by matters such as the target of the toddler health cadres and the training that were proceeded smoothly, the 90% attendance of cadres, and the significant improvement of knowledge and skills that were showed through the training and mentoring of toddler health cadres